Azimuthal distribution of quark-antiquark jets in DIS diffractive dissociation - Bartels, Jochen; Ewerz, Carlo (Physics letters, 1999)
We investigate the azimuthal distribution of quark-antiquark jets in DIS diffractive dissociation with large transverse momentum. In this kinematical region the matrix element is expressed in terms of the gluon structure function. For the transverse part of the cross section we find a cos(2φ)-distribution with the maximum at φ = ±π2, i.e. the jets prefer a direction perpendicular to the electron plane. This is in contrast to boson gluon fusion where the qq jet cross section for transversely polarized bosons peaks at φ = 0 and φ = π. We discuss the origin of this striking difference and present numerical results relevant for the diffractive dissociation at HERA.